Faktor-faktor yang Berhubungan dengan Kecemasan Menghadapi Stigma Masyarakat pada Pasien Covid-19 - Ni Rai Sintya Agustini; I Ketut Swarjana; IGNM Kusuma Negara; Ni Made Sri Rahyanti (Jurnal Kesehatan, 2022)
Covid-19 has been declared a global pandemic Anxiety is a problem that often arises in patients treated at healthcare centers or hospitals. The purpose of this study was to determine the factors related to anxiety in facing societal stigma in Covid-19 patients in the Covid-19 Isolation Room of RSD Mangusada. This research method is a quantitative study with a cross-sectional design conducted in the Covid-19 Isolation Room of RSD Mangusada in March-May 2021. The sampling technique was determined using consecutive sampling with a sample of 256 respondents. The Ordinary Logistic Regression test was used to determine the relationship between the dependent variable and the independent variable and to determine the most influential variable. The results showed that the age variable was the most influential on anxiety with a p-value of 0.049, OR=2.25, which means respondents aged 17-25 years can increase the risk of anxiety by 2.25 times compared to respondents who are adults and the elderly. Age, comorbid status, coping responses, disease-related information, and family support are factors related to patient anxiety in dealing with community stigma in Covid-19 patients at Mangusada Hospital. The involvement of all parties is absolutely necessary for dealing with the Covid-19 pandemic.